2002
DOI: 10.1002/cncr.10246
|View full text |Cite
|
Sign up to set email alerts
|

Combined intraarterial 5‐fluorouracil and subcutaneous interferon‐α therapy for advanced hepatocellular carcinoma with tumor thrombi in the major portal branches

Abstract: BACKGROUNDThe prognosis of hepatocellular carcinoma (HCC) invading into the major branches of the portal vein (Vp3) is extremely poor.METHODSEleven consecutive patients with HCC and Vp3 were treated with 2–6 cycles of a “basic” combination therapy consisting of continuous arterial infusion of 5‐fluorouracil (450–500 mg/day, for the initial 2 weeks) and subcutaneous injection of interferon‐α (5 million international units, 3 times/week, 4 weeks). In the first 3 patients, methotrexate (90 mg/day 1 of every week)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
218
2

Year Published

2004
2004
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(224 citation statements)
references
References 37 publications
4
218
2
Order By: Relevance
“…Based on this background, we experienced a patient with advanced HCC and lung metastasis, who was successfully treated with a combination therapy of IFN-a and tegafur/uracil (UFT) . In addition, we recently reported the outstanding effects of intra-arterial 5-fluorouracil (5-FU) combined with subcutaneous IFN-a for advanced HCC with tumour thrombi in the major portal branches, since 1997 (Sakon et al, 2002). Based on our results, the marked effects and acceptable toxicity of our therapy in HCC patients with extremely poor prognosis suggest that IFN-a/5-FU combination therapy is a promising treatment regimen.…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…Based on this background, we experienced a patient with advanced HCC and lung metastasis, who was successfully treated with a combination therapy of IFN-a and tegafur/uracil (UFT) . In addition, we recently reported the outstanding effects of intra-arterial 5-fluorouracil (5-FU) combined with subcutaneous IFN-a for advanced HCC with tumour thrombi in the major portal branches, since 1997 (Sakon et al, 2002). Based on our results, the marked effects and acceptable toxicity of our therapy in HCC patients with extremely poor prognosis suggest that IFN-a/5-FU combination therapy is a promising treatment regimen.…”
mentioning
confidence: 69%
“…This was a single arm open label study, based on our pervious report (Sakon et al, 2002). Between December 1997 and December 2003, 124 patients with advanced HCC and tumour thrombi in the major branches of the portal vein and multiple liver metastasis (Vp3 or 4, IM3) were diagnosed in our department.…”
Section: Patients and Selection Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…However, none of these local treatments are suitable for patients whose HCC has invaded the portal vein. Recent studies have suggested that these patients may be effectively treated by combination therapy involving subcutaneous (s.c.) administration of interferon (IFN)-a and intrahepatic administration of 5-fluorouracil (5-FU) (Sakon et al, 2002;Obi et al, 2006). A Phase II trial has also revealed that continuous 5-FU infusion combined with thrice-weekly treatment with IFN-a effectively treats HCC, perhaps because the drugs together play a neoadjuvant role (Patt et al, 2003).…”
mentioning
confidence: 99%